Observation of photonic band-gap control in one-dimensional Bragg structures - Konoplev, I; McGrane, P; Phelps, A; Cross, A; Ronald, K (2005)
The results of experimental studies of scattering and interference of waves in one-dimensional photonic band-gap structures based on coaxial waveguides with corrugated inner and outer conductors are presented. Using numerical simulations and experimental measurements, the possibility to control the band-gap parameters is demonstrated. The experimental and theoretical results obtained are compared and discussed. It is shown that the variation of the relative phase of the one-dimensional corrugations with respect to each other results in a change of the band-gap parameters in accordance with simulated predictions. © 2005 American Institute of Physics.